Early North African Christianity : turning points in the development of the church /. - Eastman, David L. (Grand Rapids, Michigan : : Baker Academic, a division of Baker Publishing Group, 2021)
"An internationally recognized scholar zeroes in on five key moments in history to show how the North African church significantly shaped Christian theology, identity, and practice in ways that still directly impact the church today"-- Provided by publisher.
Perpetua and Felicity -- Tertullian -- Cyprian of Carthage -- The Donatist controversy -- Augustine of Hippo
Includes bibliographical references (pages 169-172) and index.
Keywords: Church history--Primitive and early church, ca. 30-600.; Africa, North--Church history